Instagram Personal Branding Positions Anies Baswedan as Humanistic Public Intellectual: Personal Branding Instagram Posisikan Anies Baswedan sebagai Intelektual Publik yang Humanistik - Muhamamd Khafid Al-Furqon; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Social media has become a fundamental platform for public figures to construct digital identity and communicate political narratives through interactive visual content. Specific Background: Instagram is widely utilized in Indonesia as a strategic medium for political communication and personal branding, particularly by political actors seeking to maintain public engagement in the post-electoral phase. Knowledge Gap: Previous studies primarily examine personal branding strategies during electoral campaigns, while limited research investigates identity repositioning of political figures after electoral contests. Aims: This study aims to analyze the personal branding strategy of Anies Baswedan through the Instagram account @aniesbaswedan following the 2024 Presidential Election using Peter Montoya’s Eight Laws of Personal Branding framework. Results: Using a qualitative netnographic approach, the findings indicate that Instagram content portrays Anies as a public intellectual, educator, and humanistic leader through academic activities, social engagement, and reflective political narratives. High audience interaction demonstrates public appreciation of intellectual capacity, social concern, and communication consistency. The most dominant elements identified are unity, reflected in solidarity-based content, and persistence, shown through continuous academic engagement and consistent digital communication. Novelty: This study provides a post-election analysis of political personal branding using netnography to interpret online community responses and digital cultural interaction. Implications: The findings contribute to political communication and digital branding literature by demonstrating how social media supports identity sustainability, emotional engagement, and credibility formation of political figures beyond formal political positions. Highlights: Online Community Responses Reveal Strong Appreciation Toward Intellectual Narrative and Social Empathy. Digital Interaction Patterns Demonstrate Sustained Audience Engagement After Electoral Competition. Content Emphasizing Solidarity and Academic Participation Strengthens Leader Perception Within Virtual Communities. Keywords: Personal Branding, Instagram Political Communication, Digital Political Identity, Netnography Analysis, Political Leadership Representation